Depositor Behavior and Market Discipline in Colombia - Steiner, Roberto (IMF Working Papers; Working Paper ;, 2000)
This study examines how depositors choose among different banks and over time in Colombia, focusing on whether they discipline bank behavior. By controlling for a more comprehensive set of risk/return factors, the study improves upon conventional market discipline tests. Panel data estimations for 1985-99 show that depositors prefer banks with stronger fundamentals, and that banks tend to improve their fundamentals after being 'punished' by depositors. Banks with stronger fundamentals benefit from lower interest costs and higher lending rates. Market (or 'regulatory') discipline therefore appears to exist in Colombia, perhaps thanks to certain key design features of the deposit insurance scheme.